CLN6 deficiency causes selective changes in the lysosomal protein composition. Issue 19 (9th September 2021) - Tuermer, Andreas; Mausbach, Simone; Kaade, Edgar; Damme, Markus; Sylvester, Marc; Gieselmann, Volkmar; Thelen, Melanie
Abstract: Neuronal ceroid lipofuscinoses (NCLs) collectively account for the highest prevalence of inherited neurodegenerative diseases in childhood. This disease group is classified by the deposition of similar autofluorescence storage material in lysosomes that is accompanied by seizures, blindness and premature mortality in later disease stages. Defects in several genes affecting various proteins lead to NCL, one of them being CLN6, a transmembrane protein resident in the endoplasmic reticulum. Dysfunctionality of CLN6 causes variant late infantile NCL (vLINCL). The function of CLN6 and how its deficiency affects lysosomal integrity remains unknown. In this work, we performed a comparative proteomic analysis of isolated lysosomal fractions from liver tissue of nclf mice, a natural mouse model displaying a similar disease course than its human counterpart. We could identify a drastic reduction in the protein amounts of selected lysosomal proteins, amongst them several members of the NCL protein family. Most of these proteins were N‐glycosylated, soluble hydrolases and their reduction in protein levels was verified by western blotting and enzymatic assays. Hereby we could directly link Cln6 dysfunction to changes in the lysosomal compartment and to other NCL forms.